Clinical studies of tosufloxacin on chronic bacterial prostatitis - Ikeuchi, T (Hinyokika kiyo. Acta urologica Japonica, 1993)
In a multicenter trial at 17 institutions, the usefulness of an oral dose of 300 mg of tosufloxacin (TFLX) twice a day for 14 days were assessed in the management of chronic bacterial prostatitis (CBP) diagnosed by Meares and Stamey method. Nineteen patients who were evaluated by the UTI criteria were chosen out of the 27 patients diagnosed with CBP. The isolated bacteria from EPS were 18 species and 27 strains. In terms of MICs of isolates, TFLX gave lower MICs than any of the control drugs (CPFX, NFLX, OFLX, CCL). In particular, this tendency was clear for gram-positive coccus and anaerobes. The bacteriological elimination rate obtained for 14 strains and 19 species was 89.5% (17/19) [GPC; 75.0% (6/8), GNR; 100% (7/7), Anaerobes; 100% (4/4)]. The overall clinical efficacy by the UTI criteria was documented in 94.7% (18/19). According to the doctor's evaluation, the overall clinical efficacy rate was 68.4%. Safety evaluation revealed the development of gastrointestinal symptoms in 3 cases, which were not serious, with an incidence rate of 4.0% (3/75), while no laboratory abnormalities were observed. Transference of TFLX into the prostate is slightly lower than in other new quinolones. However, from this study we considered that the higher antibacterial activity of TFLX is one of the reasons for its usefulness for CBP